What works? Prevention and control of sexually transmitted infections and blood-borne viruses in migrants from sub-saharan Africa, Northeast Asia and Southeast Asia living in high-income countries: A systematic review - Ghimire, S.; Hallett, Jonathan; Gray, Corie; Lobo, Roanna; Crawford, Gemma (MDPI, 2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Migration is a significant risk factor for the acquisition of human immunodeficiency virus (HIV), hepatitis B virus (HBV) and other sexually transmitted infections (STIs). An increasing proportion of these infections in high-income countries, such as Australia, are among migrants moving from low and middle-income countries with a high prevalence of HIV, HBV and other STIs. This systematic review explored the prevention and control of HIV, HBV and other STIs in migrants (>18 years) from Southeast Asia, Northeast Asia and sub-Saharan Africa living in high-income countries with universal health care. This systematic review followed PRISMA guidelines and was registered with PROSPERO. Six academic databases were searched for articles published between 2002 and 2018. Sixteen peer-reviewed articles met the inclusion criteria, consisting of fourteen quantitative and two qualitative studies conducted in Australia, the Netherlands, Canada, Spain, Italy, and Germany. Three levels of interventions were identified: individual, community and structural interventions. Most studies addressed factors at an individual level; interventions were most commonly outreach testing for HIV, HBV and other STIs. Few studies addressed structural factors or demonstrated comprehensive evaluation of interventions. Limited population-specific findings could be determined. To prevent further transmission of HIV, HBV and other STIs, comprehensive public health approaches must consider the complex interactions between migration, health care system determinants, and broader socioeconomic and sociocultural factors.